Herbicide Selectivity In Eucalyptus Influenced By Spraying Nozzles - Silva,Luiz Eduardo (2019)
ABSTRACT The objective of this study was to verify the influence of spraying nozzles on the selectivity of herbicides in eucalyptus seedlings. XR 110.02 and TTI 110.02 spraying nozzles were used for the application of the herbicides: control treatment; oxyfluorfen (150 g ha–1) and saflufenacil (98 g ha–1). The experimental arrangement was a 2 × 3 factorial one (two spraying nozzles × 3 herbicides), using a randomized complete block design with four replications. The application was performed 15 days after transplanting the seedlings. Plant height (PH), stem diameter (SD), number of leaves (NL), total dry matter (DM), leaf area (LA), visual phytotoxicity (P), quantum efficiency of photosystem II - Fv/Fm, electron transport rate (ETR) and SPAD (S) index were evaluated. The XR 110.02 and TTI 110.02 nozzles did not change the selectivity of oxyfluorfen and saflufenacil.